2020
DOI: 10.1177/0734282920947504
|View full text |Cite
|
Sign up to set email alerts
|

Development of the School Mental Health Self-Efficacy Teacher Survey Using Rasch Analysis

Abstract: Given the important role that teachers play in supporting student mental health, it is critical teachers feel confident in their ability to fill such roles. To inform strategies intended to improve teacher confidence in supporting student mental health, a psychometrically sound tool assessing teacher school mental health self-efficacy is needed. The current article details the initial development and psychometric functioning of the school mental health self-efficacy teacher survey (SMH-SETS). A component of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
(65 reference statements)
2
17
0
Order By: Relevance
“…By doing so, the Rasch model produces sample-free item calibrations or item-free person measures that are essential for the fundamental measurement (Bond et al, 2020). Due to its theoretical advantages in dealing with ordinal data collected through Likert-type instruments, Rasch analysis has been widely applied in empirical studies to scrutinize the quality of instruments (e.g., Antipkina & Ludlow, 2020; Brann et al, 2021; Yan, 2018, 2020). Multiple indicators were used to examine scale quality, including response category functioning, item fit statistics (i.e., Infit MNSQ and Outfit MNSQ), and differential item functioning (DIF) across gender, educational level (primary vs. secondary), and region (Hong Kong vs. Italy).…”
Section: Methodsmentioning
confidence: 99%
“…By doing so, the Rasch model produces sample-free item calibrations or item-free person measures that are essential for the fundamental measurement (Bond et al, 2020). Due to its theoretical advantages in dealing with ordinal data collected through Likert-type instruments, Rasch analysis has been widely applied in empirical studies to scrutinize the quality of instruments (e.g., Antipkina & Ludlow, 2020; Brann et al, 2021; Yan, 2018, 2020). Multiple indicators were used to examine scale quality, including response category functioning, item fit statistics (i.e., Infit MNSQ and Outfit MNSQ), and differential item functioning (DIF) across gender, educational level (primary vs. secondary), and region (Hong Kong vs. Italy).…”
Section: Methodsmentioning
confidence: 99%
“…The School Mental Health Self-Efficacy Teacher Survey (SMH-SETS) [ 44 ] will be completed by classroom teachers. The SMH-SETS is a psychometrically sound 15 item measure that utilises a 6-point Likert scale that addresses teacher’s confidence in their ability to successfully support students’ mental health with excellent internal consistency (Cronbach’s alpha = .91), item reliability and validity [ 55 ].…”
Section: Primary and Secondary Outcomes And Measuresmentioning
confidence: 99%
“…We based the sample size calculation on the primary study objective of detecting the impact of the MHWC model on classroom teachers’ self-reported confidence to support student mental health and wellbeing which is assessed by the School Mental Health Self-Efficacy Teacher Survey (SMH-SETS [ 55 ]). We assumed a mean SMH-SETS score of 67.7 (standard deviation = 9.5) in the BAU arm based on unpublished data provided by the measure authors [ 56 ].…”
Section: Primary and Secondary Outcomes And Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wright map (figure 1) presents that the SRAVZ items are plotted on a vertical line representing the logit scale of the instrument. Items plotted at the base of the Wright map are items that are easier to agree with than items plotted toward the top of the Wright Map (Brann et al, 2020). The Wright map showed that the most difficult item was S3 (logit: 1.51), which came from the lecture planning construct.…”
Section: Based On Tablementioning
confidence: 99%